Burnout and motivation to study medicine among students during the COVID-19 pandemic - Metakides, Clio; Pielemeier, Lena; Lytras, Theodore; Mytilinaios, Dimitrios G.; Themistocleous, Sophia C.; Pieridi, Chryso; Tsioutis, Constantinos; Johnson, Elizabeth O.; Ntourakis, Dimitrios; Nikas, Ilias P. (Frontiers in Medicine, 2023)
Aim To investigate medical students’ burnout and motivation levels in each of the six years of their studies during the COVID-19 pandemic and identify independent predictors of burnout and motivation. Methods An anonymous cross-sectional survey was sent to the students of all six years within our school. Burnout was measured with the adapted Oldenburg Burnout Inventory questionnaire (OLBI-S) and motivation with the updated Strength of Motivation for Medical School (SMMS-R) questionnaire. Univariate analysis was performed with the Kruskal–Wallis test and Spearman’s correlation, while multivariable analysis with linear regression models. Results A total of 333 medical students (52% of student body) responded. Higher burnout levels correlated with lower motivation to study medicine (rho = −0.30, p < 0.001). Burnout levels differed between the six years of medical studies, peaking in years two and four whereas being the lowest in year one (p = 0.01). Motivation levels differed significantly as well, peaking in years one and four whereas being the lowest in years five and six (p = 0.012). In the multivariable linear regression models, being a female (b = 2.22, p = 0.016), studying in the fourth year vs. first year (b = 2.54, p = 0.049), having a perceived beginner/intermediate vs. advanced/expert technology level (b = 2.05, p = 0.032) and a perceived poor school support system (b = 6.35, p < 0.001) were independently associated with higher burnout levels. Furthermore, studying in the fifth year vs. first year (b = −5.17, p = 0.019) and a perceived poor school support system (b = −3.09, p = 0.01) were independently associated with a reduced motivation to study medicine. Conclusion Our study highlighted potential areas for intervention to decrease the rate of burnout and low motivation among medical students. However, further research is needed to unravel the full effect of the pandemic on medical students.